Digital unstructured data leverage using mongo DB and python - T. Mary Theresa Rani, P; S. Prasanna, Dr (International Journal of Engineering and Technology, 2018)
Every human being creates massive unstructured data every day with the technology growth. Investors to gain digital business should use these data. They will need this data for reaching the global market. In this paper, we will analyze the category of unstructured data and the way it is processed using MongoDB and Python. We will discuss using case study and derive the mechanism of faster and flexible data accessing methodology to support the Organization. Â